Design and in-silico studies of abacavir analogues as Anti-DENV-2 NS5 methyltransferase - Roney, Miah; Mohd Fadhlizil Fasihi, Mohd Aluwi (AMG Transcend Association, 2025)
Researchers have demonstrated substantial biological activity of the FDA-approved antiHIV drug "abacavir" against the cancer cell line and SARS-CoV-2. Using computational analysis, the most potent abacavir analogs were chosen in this investigation to find an anti-DENV inhibitor against the DENV-2 NS MTase. Twenty-four (24) compounds were collected through the SwissSimilarity program, and four of them were submitted to molecular docking research based on the similarity score (1.000 to 0.400). According to the studies, DB02947 has been identified as a lead molecule against DENV-2 NS5 MTase with a binding affinity of -7.4 kcal/mol and high druggability ratings. To find and discover a novel medicine to treat DENV, in vitro and in vivo experiments on DB02947 are advised to be conducted to ascertain its antiviral efficacy.